Lesson for the future climate migration. A study of relocation and development of new settlements in urban peripheries based on spatial dispersion of forced migrants in Serbia between 1991 and 2021 - Chodorowski, Michał; Božilović, Jelena; Adamski, Jakub; Messyasz, Karolina; Rekść, Magdalena; Milošević, Vuk; Ilić, Ana (Balcanica Posnaniensia. Acta et studia, 2024)
Climate migrations are going to affect the spatial structure in many regions of the world. We are now able to research long-term displacement and its spatial effects. Using the example of Serbia and the 30-year history of migration after the conflicts connected with the collapse of the former Yugoslavia, the article analyses the accompanying processes. The aim of this article is to study the spatial effects of long-term (forced) migration. The research is based on sociological and spatial planning methods, i.e. statistical data, geospatial information and institutional document analysis. The analyses show social and spatial trends in migration and settlement formation in Serbia between 1991 and 2021.